Prevalence, clinical manifestations and predictors of immune reconstitution inflammatory syndrome among HIV-infected patients in Malaysia infectious disease centre: a retrospective study - Kamarudin, Nurul Suhaili; Mohd Taib, Niazlin; Zaini, Adilahtul Bushro; Mahayidin, Hasni (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2020)
Introduction: Immune reconstitution inflammatory syndrome (IRIS) is paradoxical clinical deterioration experienced by some HIV-infected patients in response to antiretroviral therapy (ART). There is still limited published data on IRIS from this region including Malaysia. This study aimed to determine IRIS prevalence, clinical manifestations and possible predictors among HIV-infected patients in an infectious disease centre in Peninsular Malaysia. Method: This retrospective study was conducted in Hospital Sungai Buloh involving secondary data of 256 HIV-infected patients who were initiated on ART in the year 2017. Medical record of each patient was reviewed for up to 12 months following ART initiation to identify IRIS diagnosis which was made by the treating physician. Relevant clinical and laboratory information were retrieved from hospital electronic database. Results: IRIS has occurred in 17.6% of patients. Infections by Mycobacterium tuberculosis (53.3%), Pneumocystis jirovecii (11.1%) and Talaromyces marneffei (6.6%) were the commonest three aetiologies of IRIS. Subacute lupus erythematosus was the only non-infectious IRIS identified. Baseline HIV viral load, CD4+ T-cell count and haemoglobin level between IRIS and non-IRIS patients were significantly different. Risk of developing IRIS was increased seven times in patients with CD4+ T-cell count < 100 cells/µL and four times in patients with HIV RNA viral load > 5.5 log10 copies/ml prior to ART initiation. Conclusion: Mycobacterium tuberculosis infections were the highest IRIS manifestation. Although rare, non-infectious IRIS does occur and should be part of the differential diagnosis. Patients with positive predictors should be appropriately monitored for possible IRIS development once initiated on ART.